Ruang di dalam Ibadah Publik: Memikirkan Ulang Liturgi bagi Umat yang Terluka - Rachman, Rasid (Asosiasi Teolog Indonesia, 2024)
This article examines the critical yet understudied phenomenon of church worship services for congregants experiencing physical injury. While general worship practices have received extensive scholarly attention, the spatial and liturgical needs of wounded individuals—who worship alongside the general congregation—remain largely unexplored. These congregants, who bear wounds resulting from the actions of others and themselves alike, require dedicated spaces for healing. The absence of such spaces indicates that the church does not consider the presence of the wounded and injured, thereby preventing worship from serving its potential role in fostering restorative healing from injury. Through analyzing the experiences of stigmatization, injury, trauma, and the need for healing among both victims and perpetrator-victims, this article proposes the concept of privacy spaces for wounded congregants. In doing so, it reconceptualizes the church as one’s first home: a public domain that intentionally incorporates privacy spaces, which constitute liminal areas within the personal dimension of church life.